Hematologic parameters to predict negative cerebrospinal fluid examination results among neurologically intact patients who underwent lumbar puncture on suspicion of central nervous system infection - Ji Hwan Kim; Hong-Jik Kim; Ji Ung Na; Sang Kuk Han; Pil Cho Choi; Dong Hyuk Shin (Clinical and Experimental Emergency Medicine, 2017)
Objective Cerebrospinal fluid (CSF) examination is mandatory whenever central nervous system (CNS) infection is suspected. However, pleocytosis is not detected in a substantial number of suspected patients who undergo CSF examination. This study aimed to identify parameters that can aid in predicting negative CSF examination results (defined as a white blood cell count of <5 cells/high-power field). Methods The study included 101 neurologically intact patients who underwent lumbar puncture because of suspicion of CNS infection. Patients were divided into negative and positive CSF examination groups, and their initial blood tests were comparatively analyzed. Results The negative group had a significantly higher proportion of neutrophils in white blood cells (81.5% vs. 75.8%, P=0.012), lower proportion of lymphocytes in white blood cells (9.3% vs. 16.7%, P=0.001), a higher neutrophil-to-lymphocyte ratio (9.1 vs. 4.4, P=0.001), a lower lymphocyte-to-monocyte ratio (1.6 vs. 2.4, P=0.008), and a higher C-reactive protein level (21.0 vs. 5.0 mg/L, P<0.001) than the positive group. In the receiver-operating characteristic analysis, neutrophil-to-lymphocyte ratio and C-reactive protein had an area under the curve of >0.7, and the best cutoff values were 6.0 (accuracy 70.3%) and 12.7 mg/L (accuracy 76.2%), respectively. Conclusion The neutrophil-to-lymphocyte ratio ≥6 and C-reactive protein level ≥12.7 mg/L was significantly associated with negative CSF examination result.